Assessing the cognitive decline of people in the spectrum of AD by monitoring their activities of daily living in an IoT-enabled smart home environment: a cross-sectional pilot study - Grammatikopoulou, Margarita; Lazarou, Ioulietta; Alepopoulos, Vasilis; Mpaltadoros, Lampros; Oikonomou, Vangelis P.; Stavropoulos, Thanos G.; Nikolopoulos, Spiros; Kompatsiaris, Ioannis; Tsolaki, Magda (Frontiers in Aging Neuroscience, 2024)
Introduction Assessing functional decline related to activities of daily living (ADLs) is deemed significant for the early diagnosis of dementia. As current assessment methods for ADLs often lack the ability to capture subtle changes, technology-based approaches are perceived as advantageous. Specifically, digital biomarkers are emerging, offering a promising avenue for research, as they allow unobtrusive and objective monitoring. Methods A study was conducted with the involvement of 36 participants assigned to three known groups (Healthy Controls, participants with Subjective Cognitive Decline and participants with Mild Cognitive Impairment). Participants visited the CERTH-IT Smart Home, an environment that simulates a fully functional residence, and were asked to follow a protocol describing different ADL Tasks (namely Task 1 – Meal, Task 2 – Beverage and Task 3 – Snack Preparation). By utilizing data from fixed in-home sensors installed in the Smart Home, the identification of the performed Tasks and their derived features was explored through the developed CARL platform. Furthermore, differences between groups were investigated. Finally, overall feasibility and study satisfaction were evaluated. Results The composition of the ADLs was attainable, and differentiation among the HC group compared to the SCD and the MCI groups considering the feature “Activity Duration” in Task 1 – Meal Preparation was possible, while no difference could be noted between the SCD and the MCI groups. Discussion This ecologically valid study was determined as feasible, with participants expressing positive feedback. The findings additionally reinforce the interest and need to include people in preclinical stages of dementia in research to further evolve and develop clinically relevant digital biomarkers.